Pelayanan Taman Penitipan Anak (TPA) Amifah Islamic School - Anisah Nur; Viena Rusmiati Hasanah; Nike Kamarubiani (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Daycare is an organized care facility carried out during working hours to take care of children who do not receive complete care from their parents. The purpose of this study is that daycare is not a complement to parental care, but as a service that comes along with the times that can accommodate the dynamics of lifestyle. This study uses a qualitative approach. The results of the research are parenting services, education services, health services, nutrition services, and infrastructure services. Options regarding full day-based care designed to help mothers who are busy working all day in line with the development of the dual role phenomenon and how to fulfill learning-based childcare efforts.